Børnepenge: Om handel som netværksskabende aktivitet, særlige pengesedler og børn som forbrugere i Forschungstheaters Børnebanken - Hansen, Kamma Overgaard (K&K - Kultur og Klasse, 2017)
This contribution analyzes the interactive art project Die Kinderbank as it was displayed by the German Forschungstheater at Horsens Art Museum under the Danish title Børnebanken in February 2017. Børnebanken is analyzed as aesthetical art work as well as norm-critical experiment. The first, because the concept and scenography of Børnebanken can be seen as illustrative for idealistic conceptions of children, money, and trade. And the second, because Børnebanken with its interactive format is a potentially ‘uncontrollable’ work, which might lead to interesting clashes between the ideological point of departure and the practical reality. Clashes, which can be used to discuss, how we – in a relatively wealthy Western context – see ourselves as participants in a society of trading and comsuming, and not least how we imagine the role of our children in this society. My analysis addresses, how Forschungstheater in their set-up points towards a Marxist-socialist critique of capitalism as illustrated by Bertolt Brecht as well as a more complex concept of money as a concrete, society-constituting and -consolidating symbol as described by Viviana A. Zelizer. It also discusses how Børnebanken as an example of Nicolas Bourriaud’s concept of Relational Aesthetics is a work beyond our control. On that note, I ask the question of to what extend the discussions of money as societal phenomenon reach the primary target group: the children. My point is that the reactions of the children on the set-up of Børnebanken might point toward a critical consumer-behaviour rather than a norm-less curiousity.